(untitled) (Scientific journal of the Fergana State University, 2023)
This article examines the nature of discourse of advertising in linguistics. This article focuses on the interaction of language with advertising, its image and layout, and examines advertising persuasive strategies. It discusses main interrelationship between culture and advertising discourse. This study is not meant to exhaust all the fields of the particular discourse and does not involve to all the problems it poses. This article aims at find the basic elements of the most influential discourse of the 21st century advertising text.